Characteristics of Milkfish (Chanos chanos) Bone Gelatin Using Bromelain Enzyme Hydrolysis Method - Fitriyani Fitriyani; Zulfatun Najah; Septariawulan Kusumasari (Food ScienTech Journal, 2024)
Gelatin is a product obtained through partial hydrolysis of collagen from animal skin and bones. Milkfish is a type of fish that contains high protein, milkfish bones have 32% protein which can be used as an alternative for gelatin production. The purpose of this research was to determine the effect of soaking time and soaking temperature on the characteristics of milkfish bone gelatin. This research used the Split Plot Randomized Block Design method which consisted of 2 factors. The first factor was soaking  time with 3 levels, namely (1) 12 hours (2) 16 hours and (3) 20 hours. The second factor was soaking temperature consisting of 3 levels (1) 25o (2) 35oC (3) 45oC. The research results showed that soaking time had a significant effect on yield, ash content, pH, viscosity, L*, a*, b*, chroma and clarity. Soaking temperature has a significant effect on yield, ash content pH, viscosity, L*, a*, b*, 0Hue, chroma and clarity. There was an interaction of soaking time and temperature on yield, ash content, viscosity, L*, a*, b*, 0Hue, chroma and clarity.